A note on risk and value from an underutilized dataset: Consolidated disclosures. Issue 1 (12th March 2020) - Scordis, Nicos
Abstract: This essay highlights an underutilized source of data in insurance research: The consolidated data insurance holding companies disclose in Form 10‐K to their investors. A reinsurance example demonstrates that using consolidated data, as a complement to individual company statutory data, has the potential to extend insights gleaned from statutory data alone. Consolidated data, however, is limited to publicly traded insurers.